1984
DOI: 10.3109/00365548409070407
|View full text |Cite
|
Sign up to set email alerts
|

Possible Interferon Response in a Child with Measles Encephalitis during Immunosuppression

Abstract: A 4-yr-old boy with acute lymphoblastic leukaemia in remission developed an encephalopathy following an attenuated measles infection. He was treated with interferon and further deterioration was halted. Three weeks after interferon treatment was stopped, leukaemic blast cells reappeared in his peripheral blood and he died shortly thereafter. Aspects of diagnosis and treatment of this syndrome are discussed now that the presumptive clinical diagnosis is made more frequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Interferon-␣ has been used in 3 patients; 2 had no improvement in neurologic symptoms, and 1 improved temporarily but died soon after from underlying acute lymphoblastic leukemia. 20,21 One should maintain a high index of suspicion for MIBE in afebrile immunocompromised patients who present with focal status epilepticus. Typically, these patients have had recent measles infection or exposure; however, in our case, no history of either could be ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…Interferon-␣ has been used in 3 patients; 2 had no improvement in neurologic symptoms, and 1 improved temporarily but died soon after from underlying acute lymphoblastic leukemia. 20,21 One should maintain a high index of suspicion for MIBE in afebrile immunocompromised patients who present with focal status epilepticus. Typically, these patients have had recent measles infection or exposure; however, in our case, no history of either could be ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…"-'3 In contrast, two similar studies using dual photon absorptiometry showed only small differences in the bone mineral content of cases and controls.5 14 One interpretation of these findings is that the Singh index reflects some aspect of bone morphology that is more closely related to bone strength than is the bone mineral content as measured by photon absorptiometry.…”
mentioning
confidence: 98%
“…Simpson and Eden [55] reported the case of a 4-year-old boy with ALL in remission, who developed an encephalopathy following an attenuated measles vaccine. The boy's deterioration was halted when he was treated with interferon.…”
Section: Discussion Of Pathological Findingsmentioning
confidence: 99%